PRANAJIWA (Euchresta horsfieldii (Lesch), JENIS TANAMAN SEBAGAI BAHAN BAKU OBAT HERBAL POTENSIAL - Lukman Hakim; Yuliah _ (PROSIDING SNAST, 2018)
Pranajiwa (Euchresta horsfieldii (Lesch.) Is one type of plant that has the potential to be developed as a raw material of herbal medicine.This species grows on the coast, especially in Parang Kusumo and surroundings.These plants include those that will be planted in the type test as well as an ex-situ conservation plot in the Bunder Forest Park, Gunungkidul at the end of 2018. This research wants to know more about the status of research this type is using literature review method from book, proceedings, Journal of both print and online, supported by data of seed evaluation in seedbed in Center for Forest Biotechnology and Tree Improvement, Yogyakarta with diameter, height and robustness of seed. Evaluation of seedlings in the seedbed obtained an average diameter of 0.78 cm, average a height of 65.58 cm, and the average robustness of seeds 8.4. This parameter data shows that the seedlings are ready to plant with high robustness to be tested with other types and whether Pranajiwa species can grow well in Gunung Kidul. In addition, this ex-situ conservation plot is also an effort to conserve biodiversity for the good utilization of social, economic and cultural aspects of Yogyakarta society in the future.